Manajemen program pengembangan panca jangka, kemandirian dan kemajuan Pondok Modern Darussalam Gontor Indonesia - Katni Katni; Ayok Ariyanto; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2020)
This research is aimed at investigating the philosophical meaning of Pondok Gontor's Modern Darussalam using the management of the